Factors associated with satisfaction with social roles and activities among people with systemic sclerosis: a Scleroderma Patient-centered Intervention Network (SPIN) cohort cross-sectional study - Arsène Mekinian; Thierry Martin; Eric Hachulla; Carter Thorne; Danielle Rice; Andrea Benedetti; Brooke Levis; Virginia Steen; Paul R Fortin; Vincent Poindron; Aurélien Guffroy; David Launay; et al. (RMD Open)
Objective The objectives were to (1) compare satisfaction with social roles and activities in a large multinational systemic sclerosis (SSc) cohort to general population normative data and (2) identify sociodemographic, lifestyle and SSc disease factors associated with satisfaction with social roles and activities.Methods Participants in the Scleroderma Patient-centered Intervention Network Cohort completed the Patient Reported Outcomes Information System Version 2 satisfaction with social roles and activities domain questionnaire. Multivariable regression was used to assess associations with sociodemographic, lifestyle and disease factors.Results Among 2385 participants, mean satisfaction with social roles and activities T-score (48.1, SD=9.9) was slightly lower than the US general population (mean=50, SD=10). Factors independently associated with satisfaction were years of education (0.54 per SD, 95% CI 0.14 to 0.93); non-White race or ethnicity (−1.13, 95% CI −2.18 to –0.08); living in Canada (−1.33, 95% CI −2.40 to –0.26 (reference USA)) or the UK (−2.49, 95% CI −3.92 to –1.06); body mass index (−1.08 per SD, 95% CI −1.47 to –0.69); gastrointestinal involvement (−3.16, 95% CI −4.27 to –2.05); digital ulcers (−1.90, 95% CI −3.05 to –0.76); moderate (−1.62, 95% CI −2.78 to –0.45) or severe (−2.26, 95% CI −3.99 to –0.52) small joint contractures; interstitial lung disease (−1.11, 95% CI −1.97 to –0.25); pulmonary arterial hypertension (−2.69, 95% CI −4.08 to –1.30); rheumatoid arthritis (−2.51, 95% CI −4.28 to –0.73); and Sjogren’s syndrome (−2.42, 95% CI −3.96 to –0.88).Conclusion Mean satisfaction with social roles and activities is slightly lower in SSc than the general population and associated with multiple sociodemographic and disease factors.